2020
DOI: 10.1002/pros.23946
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel‐resistant prostate cancer cells become sensitive to gemcitabine due to the upregulation of ABCB1

Abstract: Background Docetaxel is the preferred chemotherapeutic agent for hormone‐refractory prostate cancer (PC) patients. However, patients eventually develop docetaxel resistance, and no effective treatment options are available for them. Objective We aimed to establish docetaxel resistance in castration‐resistant prostate cancer (CRPC) cell lines (DU145/TXR, PC‐3/TXR, and CWR22/TXR) and characterized transcriptional changes upon acquiring resistance to the docetaxel. Methods Human PC cells (DU145, PC‐3, CWR22) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…Based on the PSA response rate of 55% and radiologic response rate of 82%, one could expect that advanced PCa treatment may build upon combined therapy with GEM. Increased sensitivity to GEM was supposed to be associated with the upregulation of ABCB1, which in contrast played a pivotal role in the development of docetaxel resistance [55]. Even though it is still not clear whether docetaxel‐resistant patients could benefit from GEM therapy, a recent study has demonstrated that GEM may be beneficial to effectively induce tumor regression in the DR CRPC model.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the PSA response rate of 55% and radiologic response rate of 82%, one could expect that advanced PCa treatment may build upon combined therapy with GEM. Increased sensitivity to GEM was supposed to be associated with the upregulation of ABCB1, which in contrast played a pivotal role in the development of docetaxel resistance [55]. Even though it is still not clear whether docetaxel‐resistant patients could benefit from GEM therapy, a recent study has demonstrated that GEM may be beneficial to effectively induce tumor regression in the DR CRPC model.…”
Section: Discussionmentioning
confidence: 99%
“…EO771 mouse mammary tumor cells (CH3 BioSystems, Amherst, NY, USA), 4T1.2 mouse mammary tumor cells (obtained from Dr. R. Anderson at Peter MacCallum Cancer Institute, Melbourne, Australia), PANC-1 human pancreatic cancer cells (ATCC), and MCF-7 human estrogen receptor (ER)-positive breast cancer cells (ATCC) were cultured in DMEM (MT10013CV, Thermo Fisher Scientific). TRAMP-C2ras prostate tumor cells (ATCC) were cultured in DMEM/F-12 13 , and MDA-MB-231 human estrogen receptor (ER)-negative breast cancer cells and PC-3 human prostate cancer cells (ATCC) were cultured in RPMI-1640 (15040CV, Corning, Glendale, Arizona, USA) 14 , 15 . As non-tumor control cells, two epithelium lines (KTB36 and KTB6, obtained from Dr. H. Nakshatri, Indiana University) with the breast epithelial origin were cultured in F12-DMEM (low glucose) in a 3:1 ratio.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the results also showed that mutated TNXB only existed in the low-expression group of PRAD, while a high expression level of TNXB is correlated with a good survival prognosis in many cancers ( 61 ). Similarly, mutated ABCB1 was also found only in the low-expression group of PRAD, and it has been widely identified to take part in drug resistance of PRAD patients ( 62 64 ). Not only did ZNF419 employ mutated genes to participate in tumorigenesis and tumor progression, but epigenetic regulation also played an indispensable role.…”
Section: Discussionmentioning
confidence: 98%